Lykkeimperativet i folkeskolen - Karen Vallgårda; Caroline Nyvang (Tidsskrift for Professionsstudier, 2018)
From the perspective of emotions and childhood history, the article discusses the well-being questionnaires that are distributed to pupils in their first year of school in the Copenhagen municipality. It argues that the questionnaires make the pupils objects of emotional formation and help communicate and reinforce a norm of the happy child. This norm, which has become increasingly dominant over the past century, is linked to a growing societal focus on children’s welfare. Nevertheless, it may have unhappy consequences for the child, who is encouraged to monitor and regulate their own emotions in relation to an unattainable ideal.